Implementasi Bimbingan Vokasional Melalui Keterampilan Otomotif Roda Dua Untuk Pecandu NAPZA Usia Produktif Sebagai Bekal Keterampilan Pasca Rehabilitasi - Rendi Pidura (Department of Islamic Guidance and Counseling, 2021)
This research is motivated because there are still relapses or relapses of productive age drug addicts after entering the post-rehabilitation stage and this research is also a provision of skills for drug addicts and as a place to shift focus and channel their emotional condition after completing rehabilitation. Based on this, this research will discuss and find out how to implement vocational guidance through wheeled automotive skills. This research is a field research which is analyzed using descriptive qualitative method. Data collection techniques were carried out through interviews, observations, and documentation related to what the researchers did. The results of this study indicate that there are 3 stages of vocational guidance through two-wheeled automotive skills, namely the initial stage: assessment, building relationships and agreeing contracts. The core stage is divided into 5 stages of work, namely: knowing what the client wants in what field, looking for cooperation links, offering training and making contracts, holding debriefing, accompanying and directing clients through training. Core stage: follow-up.